Floristic survey of vascular plants of a poorly known area in the Brazilian Atlantic Forest (Flona do Rio Preto, Espírito Santo) - Alves-Araujo A. (2022)
© $$ Alves-Araújo A et al. All Rights Reserved.Background The Atlantic Forest is one of the most threatened biomes in the world. Despite that, this biome still includes many areas that are poorly known floristically, including several protected areas, such as the "Floresta Nacional do Rio Preto" ("Flona do Rio Preto"), located in the Brazilian State of Espírito Santo. This study used a published vascular plant species list for this protected area from the "Catálogo de Plantas das Unidades de Conservação do Brasil" as the basis to synthesise the species richness, endemism, conservation and new species occurrences found in the "Flona do Rio Preto". New information The published list of vascular plants was based on field expeditions conducted between 2018 and 2020 and data obtained from herbarium collections available in online databases. Overall, 722 species were documented for the "Flona do Rio Preto", 711 of which are native to Brazil and 349 are endemic to the Atlantic Forest. In addition, 60 species are geographically disjunct between the Atlantic and the Amazon Forests. Most of the documented species are woody and more than 50% of these are trees. Twenty-three species are threatened (CR, EN and VU), while five are Data Deficient (DD). Thirty-two species are new records for the State of Espirito Santo. Our results expand the knowledge of the flora of the Atlantic Forest and provide support for the development of new conservation policies for this protected area.